Role of Information and Communication Technology towards the Evolution of Digital India - Jeyraj, Sundari (Voices of Teachers and Teacher Educators, 2020)
In this digital era, Information and Communication Technology (ICT) plays a vital role in our day to day life. It refers to that form of technology, which are used to communicate, store, generate, share, exchange valuable knowledge and skills around computing and communications devices. It helps peoples to access service/information regardless of geographical distance through Internet. It also acts a driver of economic development and social progress. ICT revolution globally is measured as with the help of Networked Readiness Index (NRI), which reflect the growing importance of technology and innovation across the world. As per the World Economic Forum, out of 139 economies where NRI was measured, Singapore ranks first and India holds 91st rank. According to World Economic forum “Political and regulatory environment, Business and innovation environment, Infrastructure, Affordability, Skills, Individual usage, Business usage, Government usage, Economic impacts, Social impacts” are the sub-index of ICT. If these sub-indexes are strong, ICT become very effective which in turn will be reflected in the economy. Majority of Indian people relay on government welfare payments such as the National Rural Employment Guarantee Act, widow pensions, old age pensions, scholarships, discounted LPG cooking gas, and other subsidies. Digital payment is being encouraged as part of digitization initiatives of the Government. Electronic Payment Framework was laid down and is followed by all Ministries/ Departments and their attached Institutions/PSUs and is applicable on all Central Sector (CS)/ Centrally Sponsored Schemes (CSS) and for all schemes where components of cash is transferred to individual beneficiaries. Hence, the current paper focuses on the Role of ICTs in socioeconomic development for which secondary data and reports are used from World Economic Forum, Measuring the Information Society Report 2017 - Volume 2, MSME report, ICT indicators database etc., with simple charts and tables the role of ICT in the development process of the economy is discussed and based on the result, policy suggestions are provided.